Analisis Faktor-Faktor Yang Mempengaruhi Perataan Laba Pada Perusahaan LQ45 Yang Terdaftar di Bursa Efek Indonesia (BEI) - B41108128, Desy Sonya Pebriyanti (Jurnal KIAFE, 2014)
Income smoothing is defined as a form of earning management taken by the managers to reduce the earning fluctuation. By doing income smoothing, the company will produce stable earnings thatexpected to have beneficial effects to evaluate the management performance. The purpose of this study is to examine the influences of profitability, net profit margin (NPM), debt-to-equity ratio (DER), and firm size on the implementation of income smoothing in LQ45 companies listed in Indonesia Stock Exchange (IDX). The study conducted by using purposive sampling method and are 18 companies fulfilled the criteria. This study used Eckel index as an indicator of the occurrence of income smoothing. The analysis technique used in this study is multiple regression analysis by using SPSS after classical assumption test. The results of the study showed that profitability and debt-to-equity ratio partially have negative and unsignificant influenced in income smoothing, and the net profit margin, leverage and firm size partially have positive and unsignificant influence in income smoothing. Key Word : Profitability, Net Profit Margin(NPM),debt to equity ratio (DER), Firm size, Income smoothing, Eckel Index